The Tradition of Woman's Circumcision (A Case Study in Osing Society Banyuwangi East Java Indonesia) - Siti Khodijah; M Syamsudini (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2023)
Abstract: In Islam, a man is required to do the circumcision. Yet, in some areas, the circumcision is not only applied to the man, but also to woman. However, the practice of woman circumcision cannot be separated from tradition and religious influences. One of the portraits of community traditions that reflect the relationship between tradition and religious understanding in the Osing society, Banyuwangi, is a tradition of woman circumcision which is held as a manifestation of their religious understanding. This research is a qualitative research, so the main data source are words and actions. In collecting the data, it used participant observation, in-depth interviews) and document review. The results of this research are: Woman's circumcision activities in Osing society, Banyuwangi is still perpetuate the tradition of the practice of woman circumcision. Most of people have circumcised their daughters after birth. This activity is carried out before they are puberty, since when they grow up, they will be afraid, embarrassed and did not want to be circumcised. In addition, since, the circumcion is conducted by the midwives, there are two processes of circumcision for woman in this tribe; first is they just scratch the clitoris without cutting it, and the second is they cut the clitoris itself as man circumcision. The reason why this tradition is still exist is to perpetuate patriarchal culture for the benefit and pleasure of men. Moreover, this action to build the existence of women to be more Islamic.